MAKTAB YOSHIDAGI O'QUVCHILARNING AXLOQIY PSIXOLOGIK SIFATLARINI SHAKLLANTIRISH (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article discusses the process of forming moral skills of school-age students at that very period and developing this quality in the social environment and in the community, turning this psychological aspect into a normal state in the circle of friends, and the role and importance of teachers and parents in this process.